Participação da ativação da via IL-33/ST2 na lesão intestinal em camundongos infectados com Schistosoma mansoni - Laura Liana Maggi Fernandes (2016)
The morbidity of chronic schistosomiasis has been linked to the intensity of cellular response induced by the antigens released by the parasite eggs which are retained in host tissues, especially the liver and intestine. The granuloma formation depends on the induction of Th2 response, which participates in the elimination of eggs in remodeling of damaged tissues and containment of harmful action from parasite antigens to host tissues, but can also cause fibrosis and contribute to development the severe form of the disease. It has been shown that IL-33 cytokine, produced by endothelial cells, epithelial cells and fibroblasts during the innate immune response, stimulates the early production of IL-13 and IL-5, supporting the differentiation of Th2 response, and enhance the formation of fibrosis and infiltration of neutrophils. However, the participation of the activation of the IL-33 / ST2 in the evolution of intestinal schistosomiasis has not been reported to date and is the goal of this study. For this we used non-disabled Balb/c mice WT and a Balb/ c strain genetically deficient in expression of the receptor IL-33, called ST2 (ST2-/-). The animals were infected subcutaneously with S. mansoni cercariae and comparatively examined for 14 weeks to evaluate mortality, parasite load, immunological changes and morbidity (intestinal lesions, body weight, hematological and nutritional parameters). The data indicate that ST2-/- mice infected with S. mansoni showed increased mortality rate compared to WT. The most severe form of schistosomiasis was not associated with parasitic load or bacteria translocation and sepsis. In both experimental groups schistosomiasis also induced anemia, especially in the acute phase. However, in the absence of ST2 receptor, mice with acute schistosomiasis decreased the number of platelets and was not observed increase in circulating leukocytes. In the intestine, the absence of activation of the IL-33/ST2 resulted in increase in the retention of parasite eggs and a significant reduction of the concentration of IL-17 and Th2 cytokines, and therefore less infiltration of neutrophils and eosinophils in the acute phase of granulomas. This initial change resulted in intestinal chronic granulomas with intense cellular infiltrate, lower arginase-1 activity and disorganization of extracellular matrix deposition, which suggest an inadequate differentiation in alternatively activated macrophages. ST2-/- infected mice also showed higher frequency of occult blood in the stool and sudden weight loss. The data suggest that the activation of the IL-33 / ST2 participates in the activation of the Th2 response induced by deposition of S. mansoni eggs and assists the mechanisms of granuloma modulation and tissue remodeling that are important for intestinal mucosal protection and reduction of morbidity during infection with S. mansoni.